Early Childhood Development Operations in Latin and Caribbean Region (LCR) : Jamaica, Mexico, and Brazil in Focus - Holland, Peter; Evans, David (World Bank, Washington, DC, 2012)
The rationale and evidence of the effectiveness of investing early in children is compelling: early childhood is the most rapid period of development in a human life, with incredible brain development occurring (85 percent of the brain is wired by age 5). Investments in Early Childhood Development (ECD) are among the most effective and cost-effective investments a country can make in its people. Simply put, investing in ECD is an investment for life. Children who participate in ECD programs demonstrate improved school readiness, success, and completion; improved health; reduced risky behavior and crime; and higher productivity and income. Perhaps most importantly for public policy, delays in early childhood are difficult and costly to reverse later in life. The World Bank is particularly well-poised to help clients further the ECD agenda in their countries and improve medium and long-term development for generations to come. Given the inherently multi-sectoral nature of ECD interventions, including inter alia health, education, social protection, and the water sectors, the Bank also multi-sectoral in nature has a comparative advantage in working in this area, and can truly be more than the sum of its parts leveraging its deep sectoral expertise on issues from water and urban development to education and health and creating synergies across those areas. This note discusses how the Bank can work with clients to develop the policies and strategies for comprehensive child development, and to scale-up quality services to children. It presents case studies from three diverse countries and highlights a wide range of the types of operations offered: a multi-sector investment project with disbursements linked to specific results achieved in Jamaica, a traditional sector-specific project in Mexico, and a program of impact evaluations in Brazil. The purpose is to demonstrate the variety of instruments the Bank has, and the tailored approach that the Bank uses to respond to specific client demands for collaborating in the area of ECD.